2004
DOI: 10.1002/app.20508
|View full text |Cite
|
Sign up to set email alerts
|

Continuous ultrasonic devulcanization of unfilled butadiene rubber

Abstract: ABSTRACT:The devulcanization of sulfur-cured unfilled butadiene rubber (BR) with a grooved-barrel ultrasonic reactor under various processing conditions was carried out. The experiments indicated that BR had a narrow devulcanization window. Outside this window, significant degradation or no devulcanization occurred. Gel permeation chromatography (GPC) measurements were carried out with the sol part of virgin and devulcanized samples to study the breakdown of the polymeric chains. The GPC data showed a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
3
18
1
Order By: Relevance
“…A very narrow devulcanization window was also observed for BR 21. However, for BR, because of high unsaturation, this was caused by preferential degradation under the conditions of devulcanization.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…A very narrow devulcanization window was also observed for BR 21. However, for BR, because of high unsaturation, this was caused by preferential degradation under the conditions of devulcanization.…”
Section: Resultsmentioning
confidence: 84%
“…The devulcanized rubber can be reprocessed, shaped, and revulcanized in the same way as the virgin rubber. Extensive studies of ultrasonic devulcanization have been carried out on various rubbers, including ground tire rubber (GTR),12, 13 natural rubber (NR),14, 15 silicone rubber,16, 17 styrene–butadiene rubber (SBR),18 ethylene–propylene–diene rubber (EPDM),19 polyurethane rubber,20 and butadiene rubber (BR) 21…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that this parameter decreased as the residue content increased in the blends. Such a reduction can be attributed to the presence of residual vulcanization additives related to the first vulcanization reaction, which is a characteristic behavior of recycled rubbers [25,[34][35][36]. According to Ismail et al [36], the residual accelerator can act as a sulphur donor, which speeds up the early stages of the vulcanization process and reduces the value of ts 1 .…”
Section: Vulcanization Characteristicsmentioning
confidence: 99%
“…This technique is widely mentioned by the literature to detect the status of devulcanization of elastomers 4,5,[14][15][16]24,31,32,39,41,[43][44][45][46][47][48][49][50][51][52] . In general, the content of soluble material (sol) increases with the increasing of devulcanization degree, due to the breaks of the cross-linkings and, consequently, the release of these molecules from the three-dimensional network of vulcanized rubber.…”
Section: Introductionmentioning
confidence: 99%